ANALYSIS OF WORKLOAD ON THE QUALITY OF HEALTH SERVICES AND ITS IMPLICATIONS ON EMPLOYEE PERFORMANCE (SURVEY STUDY AT HERMINA MANADO HOSPITAL) - Saragih, Erick Gustaf Hamonangan; Yuliaty, Farida; Rasyid, Renaldi Prasetya Nagar; Kosasih, Kosasih; Rahmiyati, Ayu Laili (HEARTY, 2026)
Employee workload is a situation where employees are faced with a volume of work that must be completed at a certain time. Excessive workload can reduce employee productivity. This can lead to a decrease in the quality of health services and employee performance. This study aims to analyze workload, quality of health services and employee performance at Hermina Manado Hospital. This study uses a quantitative approach. The sample in this study amounted to 68 respondents. The data analysis used is descriptive analysis and verification analysis using path analysis. The results of the descriptive analysis of workload, quality of health services and employee performance of respondents gave a good assessment, there were still some that needed to be improved. While the results of the verification study, the path analysis model showed that the path coefficient value between variables was positive and the indirect influence path coefficient value was greater than the direct influence (73.6> 45.4%), meaning that the health service quality variable as an intervening variable was able to mediate the workload variable with the employee performance variable.